Design, fabrication and characterisation of a 24.4% efficient interdigitated back contact solar cell. (29th October 2014) - Franklin, Evan; Fong, Kean; McIntosh, Keith; Fell, Andreas; Blakers, Andrew; Kho, Teng; Walter, Daniel; Wang, Da; Zin, Ngwe; Stocks, Matthew; Wang, Er‐Chien; Grant, Nicholas; et al.
Abstract: The interdigitated back contact (IBC) solar cells developed at the Australian National University have resulted in an independently confirmed (Fraunhofer Institut für Solare Energiesysteme (ISE) CalLab) designated‐area efficiency of 24.4 ± 0.7%, featuring short‐circuit current density of 41.95 mA/cm 2, open‐circuit voltage of 703 mV and 82.7% fill factor. The cell, 2 × 2 cm 2 in area, was fabricated on a 230 µm thick 1.5 Ω cm n‐type Czochralski wafer, utilising plasma‐enhanced chemical vapour deposition (CVD) SiNx front‐surface passivation without front‐surface diffusion, rear‐side thermal oxide/low‐pressure CVD Si3 N4 passivation stack and evaporated aluminium contacts with a finger‐to‐finger pitch of 500 µm. This paper describes the design and fabrication of lab‐scale high‐efficiency IBC cells. Characterisation of optical and electronic properties of the best produced cell is made, with subsequent incorporation into 3D device modelling used to accurately quantify all losses. Loss analysis demonstrates that bulk and emitter recombination, bulk resistive and optical losses are dominant and suggests a clear route to efficiency values in excess of 25%. Additionally, laser processing is explored as a means to simplify the manufacture of IBC cells, with a confirmed efficiency value of 23.5% recorded for cells fabricated using damage‐free deep UV laser ablation for contact formation. Meanwhile all‐laser‐doped cells, where every doping and patterning step is performed by lasers, are demonstrated with a preliminary result of 19.1% conversion efficiency recorded. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : Interdigitated back contact (IBC) solar cells with a best confirmed aperture‐area efficiency value of 24.4% have been developed at the Australian National University. This paper describes the design, fabrication and characterisation of lab‐scale high‐efficiency IBC cells and uses 3D device modelling to perform detailed loss analysis of the cell and provide a clear pathway to 25%+ efficient cells. Process simplifications via laser processing are investigated, and some preliminary results for IBC cells with laser patterning and laser doping are presented.